The protection of central Africain forest écosystèmes within the test of socioeconomic development needs : the case of Cameroon - (:unkn) unknown (My University, 2019)
The forest ecosystems of Central Africa in general and those of Cameroon in particular, are very rich in natural resources. They offer many opportunities for people in terms of livelihoods. However, faced with the implementation of the process of socio-economic development, this environment is confronted with many threats including deforestation, degradation, poaching, pollution, overexploitation of biotic and abiotic resources, etc. The Cameroonian legislator, spurred by the action of international cooperation, has adopted several international legal instruments and has legislated on measures to protect forest ecosystems during the implementation of socio-economic development projects. However, a careful analysis of the normative and institutional framework put in place in Cameroon shows that the legal mechanisms for protecting forest ecosystems during the implementation of socio-economic development projects, although plural, remain ineffective and inefficient. There is still much work to be done on some aspects of legislation and enforcement of existing legal mechanisms to ensure that forest ecosystem protection objectives are effective and efficient. The problems of human and financial resources, forest governance, institutional incoordination, ecological illiteracy, widespread poverty of the people, conflict between tradition and modernity have the effect of putting into perspective the effectiveness and efficiency of the protection of forest ecosystems in Cameroon. Meeting this challenge requires the implementation of several actions, the most salient of which are the reformulation of the legislative framework, the improvement of governance and the elaboration of an international convention on forests.
Keywords: African Research